Biokonsentrasi Faktor (BCF) dan Faktor Translokasi (TF) Purun tikus (Eleocharis dulcis) dalam Fitoremediasi Air Asam Tambang - Ratu Wulandari Permatasari Putri; Poedji Loekitowati Hariani; Zainal Arifin (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Acid mine drainage is mining waste that contains a lot of sulfate and heavy metals such as Fe and Mn which can cause environmental damage and pollute the ecosystem, therefore it needs to be managed. One way to manage acid mine drainage is with phytoremediation techniques using Purun tikus (Eleocharis dulcis). The ability of Purun tikus to accumulate heavy metals can be known by calculating the bio-concentration factor (BCF) and tranclocation factor (TF). This study aims to determine the value of bio concentration factor (BCF) and tranclocation factor (TF) in rat purun in absorbing Fe and Mn so that it can be used for coal mine acid water management. Sampling was conducted using Convenience sampling method. Analysis of Fe, Mn, BCF and TF levels was carried out using an atomic absorption spectrophotometer. In the study, the bio concentration factor (BCF) value for Fe was 7.53, and for Mn was 30.09. While the value of the tranclocation factor (TF) for Fe is 0.77 or the value of TF less than 1, this indicates that rat Purun in accumulating Fe metal uses a phytostabilization mechanism. Then the tranclocation factor (TF) value for Mn is 1.44 or TF value more than 1, indicating that in accumulating Mn metal, Purun rats use a phytoextraction mechanism.